Application of Pickering emulsion-based coatings/films stabilized with chitosan nanoparticles for the preservation of fresh postharvest commodities - Wardana, Ata Aditya; Marcellino, Vincensius; Wigati, Laras Putri; Nkede, Francis Ngwane; Tanaka, Fumina; Tanaka, Fumihiko; Setiarto, R. Haryo Bimo (Frontiers in Sustainable Food Systems, 2025)
Postharvest losses of fresh produce remain a persistent challenge. Application of coatings/films have been extensively investigated as sustainable preservation strategies. This review highlights the role of chitosan nanoparticle (ChiNP)-stabilized Pickering emulsions in enhancing the functional performance of such coatings for maintaining fruit and vegetable quality. The findings indicated that ChiNP offer some advantages, including antimicrobial properties due to their cationic nature, while their nanoscale size contributes to emulsion stability by improving interfacial adsorption. Their incorporation enhances gas and water vapor barrier properties through a dense structural configuration at the oil–water interface, effectively suppressing ethylene biosynthesis and delaying cell wall degradation, thereby slowing ripening. Moreover, ChiNP demonstrate synergism with essential oils (EO), significantly improving the antimicrobial efficacy. However, further research is needed to improve stability, understand interactions with biopolymer matrices, assess wettability, ensure safety, and optimize delivery performance. In industrial context, the optimization of formulation parameters and sensory evaluations should be prioritized, thereby supporting the potential implementation of ChiNP as an effective and sustainable approach for fresh postharvest commodities preservation.